2016
DOI: 10.1158/1535-7163.mct-15-0764
|View full text |Cite
|
Sign up to set email alerts
|

SPARC-Independent Delivery of Nab-Paclitaxel without Depleting Tumor Stroma in Patient-Derived Pancreatic Cancer Xenografts

Abstract: The study goal was to examine the relationship between nab-paclitaxel delivery and SPARC (secreted protein acidic and rich in cysteine) expression in pancreatic tumor xenografts and to determine the anti-stromal effect of nab-paclitaxel, which may affect tumor vascular perfusion. SPARC positive and negative mice bearing Panc02 tumor xenografts (n=5–6/group) were injected with IRDye 800CW (IR800)-labeled nab-paclitaxel. After 24 hours, tumors were collected and stained with DL650-labeled anti-SPARC antibody, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 33 publications
3
39
0
Order By: Relevance
“…However, there are contradictory reports that raise the question of whether SPARC is associated with the therapeutic effect of Abraxane. For example, a study showed that Abraxane was preferentially delivered to tumor stromal tissue, but there was a minimal correlation between Abraxane and SPARC distribution in either SPARC‐positive or ‐negative animals, which suggested that the specific tumor delivery of Abraxane was not directly related to SPARC expression …”
Section: Biomimetic Drug Delivery Mediated By Albuminmentioning
confidence: 80%
See 1 more Smart Citation
“…However, there are contradictory reports that raise the question of whether SPARC is associated with the therapeutic effect of Abraxane. For example, a study showed that Abraxane was preferentially delivered to tumor stromal tissue, but there was a minimal correlation between Abraxane and SPARC distribution in either SPARC‐positive or ‐negative animals, which suggested that the specific tumor delivery of Abraxane was not directly related to SPARC expression …”
Section: Biomimetic Drug Delivery Mediated By Albuminmentioning
confidence: 80%
“…For example, as tudy showedt hat Abraxane was preferentially delivered to tumor stromal tissue, butt here was am inimal correlation between Abraxane and SPARC distribution in either SPARC-positive or -negative animals, which suggested that the specific tumor delivery of Abraxane was not directly relatedt oSPARC expression. [75] Figure 6. A) BBB-penetrating l-BSA NPs delivered into gliomathrough mechanisms targeting the ABP;the efficiency is furthere nhanced by cell-penetrating peptide( CPP)-assisted penetration.…”
Section: Can the Expression Level Of Abp Be Atherapeutic Biomarker Fomentioning
confidence: 99%
“…47 Further to this, Roy Chaudhuri et al investigated the effect of smoothened inhibitors of hedgehog signaling (sHHI) to overcome the stromal barrier and promote neovascularization and enhance tumor permeability to low-molecular weight compounds in a PDX model of pancreatic cancer. The authors demonstrated that sHHI can enhance tumor deposition and efficacy of drug-containing nanoparticles consisting sterically stabilized liposomes containing doxorubicin.…”
Section: Pdx Models To Assess Therapeutic Efficacymentioning
confidence: 99%
“…Nab‐PTX, approved by the Food and Drug Administration (FDA) in 2012 as the first line in neoadjuvant therapy for pancreatic cancer, is widely used in clinical work and significantly improves outcome . Taking advantage of albumin‐binding, nab‐PTX efficiently accumulates in peri‐ and intratumoral areas dependent or independent of secreted protein acidic and rich in cysteine (SPARC) mediating . Many clinical and animal studies showed that nab‐PTX treatment could disrupt tumor stroma, decrease PSC activity, and inflammatory cytokines .…”
Section: Introductionmentioning
confidence: 99%
“…8 Taking advantage of albumin-binding, nab-PTX efficiently accumulates in peri-and intratumoral areas dependent or independent of secreted protein acidic and rich in cysteine (SPARC) mediating. 9,10 Many clinical and animal studies showed that nab-PTX treatment could disrupt tumor stroma, decrease PSC activity, and inflammatory cytokines. 11 However, the role of nab-PTX in tumor cells and CAF communication is unclear.…”
Section: Introductionmentioning
confidence: 99%